Simultaneous detection of mRNA transcription and decay intermediates by dual colour single mRNA FISH on subcellular resolution - Kramer, Susanne (Nucleic Acids Res, 2017)
The detection of mRNAs undergoing transcription or decay is challenging, because both processes are fast. However, the relative proportion of an mRNA in synthesis or decay increases with mRNA size and decreases with mRNA half-life. Based on this rationale, I have exploited a 22 200 nucleotide-long, short-lived endogenous mRNA as a reporter for mRNA metabolism in trypanosomes. The extreme 5΄ and 3΄ ends were labeled with red- and green-fluorescent Affymetrix® single mRNA FISH probes, respectively. In the resulting fluorescence images, yellow spots represent intact mRNAs; red spots are mRNAs in transcription or 3΄-5΄ decay, and green spots are mRNAs in 5΄-3΄ degradation. Most red spots were nuclear and insensitive to transcriptional inhibition and thus likely transcription intermediates. Most green spots were cytoplasmic, confirming that the majority of cytoplasmic decay in trypanosomes is 5΄-3΄. The system showed the expected changes at inhibition of transcription or translation and RNAi depletion of the trypanosome homologue to the 5΄-3΄ exoribonuclease Xrn1. The method allows to monitor changes in mRNA metabolism both on cellular and on population/tissue wide levels, but also to study the subcellular localization of mRNA transcription and decay pathways. I show that the system is applicable to mammalian cells.